Exploring the relationships between narratives, emotions and transmedia strategies: Stories of the final report of the Truth Commission, a remix from the graphic design classroom (REVISTA NODO, 2023)
This article presents the exploration and experimentation carried out by the research group DAFT, belonging to the Graphic Design program at Antonio Nariño University (UAN) in Bogotá, Colombia. The main objective of this study was to investigate the relationships between narratives, emotions, and transmedia strategies in support of the stories told by the Truth Commission.Emphasis is placed on analyzing the interactions between narratives and emotions found in the final report of the Truth Commission. To support this approach, an experiment was conducted with Graphic Design students who participated in creating a remix of the stories from the final report using transmedia strategies. The analysis of the data revealed the importance of emotions in the reception and understanding of the narratives told by the Truth Commission. Additionally, different transmedia strategies used in the remix of the stories are proposed, which helped enrich the narrative experience and promote empathy with the victims.Thus, it is argued that by effectively combining narratives, emotions, and transmedia strategies, it is possible to create more impactful and meaningful experiences that contribute to the dissemination and understanding of the Truth Commission’s final report. The findings of the exploration have important implications for the practice of graphic design and social communication, highlighting the importance of considering the intersection between narratives, emotions, and transmedia strategies when addressing sensitive issues and promoting empathy in society.